2007
DOI: 10.1159/000099339
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Impact of Postoperative Urethral and Periurethral Anatomical Features in Post-Radical Retropubic Prostatectomy Incontinence?

Abstract: Objectives: To determine the anatomical changes in urethral and periurethral tissues after radical retropubic prostatectomy (RRP) by magnetic resonance imaging (MRI) and correlate these changes to continence. Materials and Methods: 14 patients with grade 2–5 incontinence and 16 continent (grade 1) patients who had undergone non-nerve-sparing RRP for clinically localized prostatic carcinoma were evaluated. The sphincteric urethral length, transverse and craniocaudal diameters of both levator ani muscles and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
0
14
2
Order By: Relevance
“…The bladder neck was identified and the angular measurement of the lumen recorded. The anatomical urethral sphincter length was measured from the bladder neck to the entry of the urethra into the penile bulb in both the sagittal and coronal planes . The urethral thickness was measured in its thickest area in three views.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bladder neck was identified and the angular measurement of the lumen recorded. The anatomical urethral sphincter length was measured from the bladder neck to the entry of the urethra into the penile bulb in both the sagittal and coronal planes . The urethral thickness was measured in its thickest area in three views.…”
Section: Methodsmentioning
confidence: 99%
“…The urethral thickness was measured in its thickest area in three views. The levator ani was measured in two views with the thickest area measured as the maximum length converging on the urethra . Measurements were made by two urologists (APC and AMS) and the values averaged.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of incontinence was evaluated using a questionnaire that graded continence level on a 5-point scale: 1 ¼ complete continence; 2 ¼ 1 pad daily; 3 ¼ 2-3 pads daily; 4 ¼ !4 pads daily; and 5 ¼ complete incontinence. 12,13 MRI Technique MRI was performed using a 1.5-T whole-body magnetic resonance scanner (Signa, GE Medical Systems, Milwaukee, WI). At 1 hour before MRI, all patients were instructed to empty the bladder and drink 1-2 glasses of water and requested to try to empty the bowels.…”
Section: Evaluation Of Luts and Urinary Function After Rpmentioning
confidence: 99%
“…12,13,15 Kordan et al 12 reported that postoperative MUL measured by pelvic MRI tends to be correlated to the degree of incontinence. Paparel et al 13 reported that longer postoperative and preoperative MUL measured by endorectal MRI were associated with superior continence.…”
Section: Commentmentioning
confidence: 99%
“…The formation of a subvesical obstruction due to bacteriuria unfortunately was not investigated [21] . Whether postoperative UTIs are a risk factor for prolonged urinary incontinence is still under debate [22,23] .…”
Section: Discussionmentioning
confidence: 99%